Pengaruh Sistem Pengendalian Internal Pemerintah dan Kompetensi Sumber Daya Manusia Terhadap Efektivitas Pengelolaan Aset Kabupaten Bandung Barat - Ade Amelia Manalu; Ivan Yudianto (Universitas 45 Surabaya, 2024)
This study aims to see how much influence the government internal control system and human resource competencies have on the effectiveness of regional asset management in West Bandung Regency. The survey in this study was conducted at 40 SKPDs in West Bandung Regency. The research method used in this research is descriptive-verification by distributing questionnaires to each SKPD as many as 40 questionnaires, with the respondents being the administrators of goods in each regional work unit. The data analysis method used is multiple linear regression assisted by SPSS version 29 software. The results of this study indicate that the Government Internal Control System has a positive and significant effect on the effectiveness of regional asset management. Human Resource Competence has no positive and significant effect on the effectiveness of asset management. The Government Internal Control System and Human Resource Competencies simultaneously have a positive and significant effect on the effectiveness of regional asset management. Government Control System and Human Resource Competencies simultaneously on the Effectiveness of Regional Asset Management of West Bandung Regency.